Coaching-Based Academic Supervision as a Strategy to Improve Teachers’ Professional Performance: A Qualitative Case Study in Secondary School - Ida Solowati; Lusi Kurniasari; Farah Amalia; Soedjono Soedjono (FKIP - Universitas Riau, 2026)
Improving teachers’ professional performance is a critical challenge in secondary education, especially when academic supervision is often perceived as administrative control rather than a developmental process. This study aims to examine the implementation of coaching-based academic supervision conducted by school principals and its role in enhancing teachers’ professional performance at SMP Negeri 9 Pekalongan. Employing a qualitative approach with a case study design, the research investigates the supervision process, teachers’ perceptions, and its impact on instructional practices. Data were collected through focus group discussions, classroom observations, and document analysis involving the principal and teachers participating in coaching-based supervision activities. The findings indicate that coaching-based academic supervision transforms supervision into a reflective and collaborative professional development process through joint goal setting, classroom observation, reflective dialogue, and post-observation reflection. This approach enhances teachers’ self-awareness, motivation, and instructional innovation, while fostering a supportive and trusting supervisory relationship. Challenges included time constraints and varying readiness of teachers to engage in reflective coaching. The study concludes that coaching-based supervision effectively improves teachers’ professional performance and builds a collaborative learning culture. Theoretically, it advances academic supervision models by integrating coaching principles; practically, it provides actionable guidance for school leaders in sustaining teacher professional development.